Price and Production Controls in World War II - Hugh Rockoff (Rutgers University, Department of Economics, 1996)
The great surge in munitions production in World War II, which reached its peak in 1943, was produced by a building boom launched in 1941 and 1942. Resources were drawn rapidly to war production centers by financial incentives and other personal and corporate motives such as patriotism. This happened while price controllers at OPA and production controllers at the WPB were still devloping their policies. Price and production controls may have accomplished many things toward the end of the war, but they cannot account for the speed and magnitude of the initial response.
Keywords: N1; N4; 330; controls; war